Mangrove forest ecosystem is an important ecosystem in a coastal area in order to improve the welfare of coastal villages as well as to improve the productivity of coastal ecosystem. The purposes of this research were (1) to identify indicators of sustainable mangrove forest ecosystem; (2) to analyze the ecological, economic and social conditions of mangrove forest ecosystem; (3) to analyze index sustainability of mangrove forest ecosystem and (4) to formulate strategies for sustainable mangrov - Debby.V. Pattimahu; Cecep Kusmana; Hartrisari Harjomidjojo; Dudung Darusman (Forum Pasca Sarjana, 2010)
Mangrove forest ecosystem is an important ecosystem in a coastal area in order to improve the welfare of coastal villages as well as to improve the productivity of coastal ecosystem.  The purposes of this research were (1) to identify indicators of sustainable mangrove forest ecosystem; (2) to analyze the ecological, economic and social conditions of mangrove forest ecosystem; (3) to analyze index sustainability of mangrove forest ecosystem and (4) to formulate strategies for sustainable mangrove forest ecosystem in Western Part of Seram, Maluku.  This research applied multidimensional scaling (MDS), leverage analysis, Monte Carlo analysis and analytical hierarchy process (AHP) to analyze data.  Research showed that dimension of ecology, economy, and social was high sustainable, low sustainable and unsustainable respectively.  Among 22 indicators analyzed there were 6 sensitive indicators which affected local sustainability index. These sensitive indicators should be improved to increase local sustainability index in the future.   Key words: mangrove sustainability indicators, mangrove sustainability index